Awareness of cancer cervix and its prevention among students in Melaka, Malaysia - Somsubhra De; Vigneshwari T Selvan; James Tan; Htoo Htoo Kyaw Soe; Soumendra Sahoo; Rashmirekha Sahoo (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Cancer cervix is caused by human papillomavirus (HPV), oncogenic virus and has vaccines and screening as its preventive measures. This study analyzes the change in awareness and attitudes of nonmedical students toward the condition following the use of an educational module. METHODOLOGY: The study design was quasi-experimental. The interprofessional (IP) team implemented an educational module and analyzed the difference in awareness of young individuals toward the cancer cervix. A pretest and posttest written questionnaire, customized for both genders, was administered with the intervention of the educational module in between. The module consisted of a short educational presentation along with a group activity. A follow-up survey was also done after 2 months to check the attrition of awareness. The statistical analysis was done using MacNemar test using SPSS 12 IBM software and significance of differences were determined. RESULTS: There was a significant improvement of knowledge and awareness on linkage between HPV and cervical cancer (P < 0.001). There was also significant change with regard to attitudes toward cervical cancer vaccination (P = 0.004). The knowledge of HPV linkage to the malignancy was maintained after 2 months of gap. The subjects also wished for more future awareness program. CONCLUSIONS: There is improved awareness in the dental and foundation in science students, and this improved awareness will ensure favorable attitudes toward cervical cancer vaccines or will attend regular screening programs. Awareness program must be held at regular intervals at different locations to enhance the knowledge dissemination of this common yet preventable genital malignancy of females. The IP collaboration and practices will help in reducing the disease burden of the society in future.